Próba artykulacji - Sztaba, Wojciech (Przestrzenie Teorii, 2010)
Sztaba Wojciech, Próba artykulacji [An Attempt at Articulation]. „Przestrzenie Teorii” 14. Poznań 2010, Adam Mickiewicz University Press, pp. 107-121. ISBN 978-83-232-2210-1. ISSN 1644-6763. Witkacy’s Pure Form expresses the metaphysical essence of art. On the one side, it symbolizes the structure of the world, the unity in plurality (which is demonstrated in the picture’s composition) and, on the other, the notion deals with the processes of creating and perceiving an art work. The moment in which the self feels itself embedded in the wholeness of the world is the moment in which the metaphysical feeling arises, and in which the experience of art is fulfilled. Witkacy provides many examples for situations evoking this feeling. He describes them in his novels, he finds synonyms as suchness, curiosity of existence, mystery of being or unity of identity, he switches from scientific to poetic language. And he emphasizes that this feeling, while defying verbalization, is a real, not a supernatural one: a psychophysical phenomenon accessible to introspection, and inseparable from one's cultural and individual background.